PENERAPAN PENDIDIKAN KARAKTER PADA ANAK USIA DINI DI TK ISLAM ASH-SHIBGOH DIDESA KALIJAGA TAHUN 2024 - Ni'Matul Khaer; Abdul Kadir Jaelani; Muhammad Tahir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the implementation of character education in early childhood at Ash-Shibgoh Islamic Kindergarten, Kalijaga Village. Character education has an important role in shaping children's personalities, especially at the age of 0-6 years which is known as the "golden age" phase. Through a qualitative descriptive approach, the subjects and objects of research are the principal and teachers while the object of research is the process of practicing character education in children. Data collection techniques used in this study used observation, interviews and documentation. The data analysis method uses an interactive model from Miles and Huberman, namely data collection, data reduction, data presentation and drawing conclusions. This study identifies the implementation of character education, supporting factors, and obstacles faced in its implementation. The results showed that the implementation of character education in Ash-Shibgoh Kindergarten was carried out through various strategies including habituation, role modeling, learning, and cooperation with parents. However, there are several challenges such as the lack of parental understanding of character education and limited resources. It can be concluded that character education can be carried out through three strategies, namely habituation, role modeling and learning and cooperation between parents and teachers.